Health Impact Assessment in a Swedish context: The Route 73 case study (Italian Journal of Public Health, 2007)
Background: Health issues are being allocated increasingly higher priority on the political agenda in Sweden, due to initiatives taken by both the Parliament (the Riksdag) and the Government over the last few years. The Riksdag has recently adopted a bill for public health.Methods: The case study was performed in accordance with the framework for the project “The effectiveness of Health Impact Assessment”, which includes a common questionnaire and a model for evaluating effectiveness. During the study, six interviewees representing different actors and stakeholders in the decision-making process were contacted. The analysis of effectiveness of the HIA on Route 73 is based on the “partial HIA”, i.e. the HIA that is incorporated into the EIA, but the case study also illustrates the benefits of performing a complementary HIA in accordance with the new guidelines in Sweden.Results: The case study on Route 73 shows that the partial HIA had general health effectiveness and general or direct community effectiveness. With respect to equity effectiveness, the answers varied. If the complementary HIA had been used as a basis instead of the partial HIA, it would have highlighted equity aspects much more since the complementary HIA focuses on priority groups and gender throughout the assessment and makes them an important part of the assessment.Conclusions: There is a growing awareness of public health in Sweden today due to the policies adopted by the Riksdag and the Government. Public health objectives, the pinpointing of prioritised groups, health determinants and indicators constitute a good framework for conducting HIA in accordance with the new public health policy and represent its prime facilitators.
Keywords: Health impact assessment (HIA); public health policy; effectiveness; hindrances to and facilitators of HI; implementation